Analysis of calcium levels in the carapace of rajungan crab (Portunus pelagicus) - Wandi, Wandi; Karim, Mutemainna; Angreni, Husni (Sangia Research Media and Publishing, 2023)
This research aims to determine differences in calcium levels in small crabs (Portunus pelagicus) in three parts, namely carapace/shell, claw feet and abdomen. This research was conducted from May to June 2023 at UD. Bumi Nusantara Pattiro Sompe, Sibulue, Bone Regency, South Sulawesi. The research method used is an experimental method. with three types of samples (abdomen, claw feet and carapace/shell), calcium level parameters with two repetitions. Data were analyzed using T-test. Based on the research results, it shows that the highest calcium levels are in the carapace/shell (46.77%), followed by the claws (41.91%), while the lowest are in the abdomen (40.76%). The conclusion of this study is that there is a significant difference in levels calcium between the carapace/shell and the abdomen and claw legs but did not differ significantly between the abdomen and claw legs.